ChemInform Abstract: A General Approach to Arylated Furans, Pyrroles, and Thiophenes. Issue 14 (April 2015) - Zheng, Qingwei; Hua, Ruimao; Jiang, Jianhua; Zhang, Lei
Abstract: Title compounds are prepared from 1, 4‐diaryl‐1, 3‐butadiynes (I) by reaction with H2 O, primary amines (III) or Na2 S, respectively.